Subscribe to our Youtube Channel - https://www.youtube.com/channel/UCZBx269Tl5Os5NHlSbVX4Kg

Last updated at March 16, 2017 by Teachoo

Transcript

Example 24 Factorize 8x3 + 27y3 + 36x2y + 54xy2 8x3 + 27y3 + 36x2y + 54xy2 = (2x)3 + (3y)3 + 36x2y + 54xy2 = (2x)3 + (3y)3 + 18xy(2x + 3y) = (2x)3 + (3y)3 + 3(2x) (3y) (2x + 3y) Using (a + b)3 = a3 + b3 + 3ab(a + b) Putting a = 2x , b = 3y = (2x + 3y)3 = (2x + 3y)(2x + 3y)(2x + 3y)

Examples

Example 1

Example 2

Example 3 Important

Example 4

Example 5

Example 6

Example 7 Important

Example 8

Example 9

Example 10

Example 11

Example 12 Important

Example 13

Example 14

Example 15 Important

Example 16

Example 17

Example 18 Important

Example 19

Example 20

Example 21 Important

Example 22

Example 23 Important

Example 24 Important You are here

Example 25

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.